Implementasi Metode Fuzzy Subtractive Clustering Untuk Pengelompokan Data Potensi Kebakaran Hutan/Lahan - Vianti Mala Anggraeni Kusuma; Muhammad Tanzil Furqon; Lailil Muflikhah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Abstract Forest is the habitat for all kinds of animals and plants, forests have a very big function to maintain the balance of nature, as the supplier of the oxygen requirement for living on earth, and the natural resources that provide a variety of materials for human needs. But at this moment the existence of forest diminishing due to illegal logging by humans or by forest fires are becoming more frequent. Forest fires this gives very bad impact, extinction of some species of plants and animals, the smoke is detrimental to health even low and so forth. So to be able to help deal with the issue made a system that can manage data hotspots (hotspots) with Fuzzy subtractive clustering. Parameter data used in the development of the system: brightness temperature and FRP (Fire Radiative Power). The result of clustering which illustrates the potential of forest fires, which are grouped in the high potential and low potential. The test results showed the best coefficient silhouette value of 0.45 and the results of the cluster is formed by two clusters using radius values â€‹â€‹0.2, accept ratio 0.5, reject ratio 0.15. The results of the analysis in the determination of the potential for forest fires result is a high potential with an average brightness value of 335.727â°K, FRP 57.248 and average confidence 83.47%. While medium potential with an average brightness value of 318.934â°K, FRP 23.330 and average confidence 58.08%. Keywords: Clustering, Hotspot, Fuzzy subtractive clustering, Silhouette Coefficient